Factors affecting performance and manufacturability of naproxen Liqui-Pellet - Lam, Matthew (Daru, 2020)
AIM: Liqui-Pellet is potentially an emerging next-generation oral pill, which has shown promising results with unique advantages as well as displaying potential for commercial feasibility. Since Liqui-Pellet technology is still in its infancy, it is important to explore the parameters that can affect its performance, particularly the drug release rate. Therefore, the aim of this study is to investigate thoroughly the effect of Avicel PH101 (carrier) and Aerosil 300 (coating material) ratio (R-value) in Liqui-Pellet. METHODS: Key parameter for Liqui-Pellet formulation in this study was the ratio of carrier and coating material. Tests were carried out to assess the physicochemical properties of different formulations. This involved looking into particle size, robustness, flowability, solid-state and drug release profile. The morphology of Liqui-Pellet was investigated by SEM. RESULTS: It is found that R-value does not have a major effect on the success of Liqui-Pellet production. However, R-value does seem to have an effect on Liqui-Pellet size at a certain water content level and a slight effect on the drug release rate. A decrease in Avicel PH101 concentration and an increase in Aerosil 300 concentration in Liqui-Pellet formulations can reduce Liqui-Pellet size and slightly increase drug release rate by 9% after 2 h. The data shows Liqui-Pellet is resistant to friability, able to achieve exceptional flow property and have smooth surfaces, which is critical for applying coatings technology. Such properties are ideal in terms of commercial manufacturing. The XRPD and DSC both show the reduction in formulation crystallinity, which is expected in Liqui-Pellet formulation as a result of solubility of the drug in the co-solvent used in the preparation of Liqui-Pellets. CONCLUSION: Overall it seems that R-value can affect Liqui-Pellet drug release rate and size but not on the production success rate. GRAPHICAL ABSTRACT: [Image: see text]